Pearl millet hybrid tolerance and weed control with preemergence herbicides - Midhat Z. Tugoo; Vipan Kumar; Sabreena A. Parray; Ajay Prasanth Ramalingam; P.V. Vara Prasad; Ramasamy Perumal (Weed Technology)
Weed management is a major challenge in pearl millet production. Limited herbicide options available for use with pearl millet further complicates weed control. To fill this knowledge gap, field experiments were conducted during the 2023 and 2024 growing seasons in Hays, Kansas, to investigate eight preemergence herbicides (labeled for use in sorghum production) for crop safety and weed control when applied to three pearl millet hybrids. Averaged across two growing seasons, S-metolachlor applied preemergence alone or in combination with atrazine, mesotrione, or atrazine + mesotrione resulted in >95% injury to all three pearl millet hybrids at 28 d after application (DAA). Visible injury with acetochlor + atrazine applied preemergence ranged from 50% to 96% among hybrids at 28 DAA. Atrazine or mesotrione applied alone or in combination were safe (<5% injury) on all hybrids. All tested preemergence herbicides provided effective (≥90%) control of Palmer amaranth at 28 DAA, except S-metolachlor, which provided 86% control. The greatest green foxtail control (≥99%) was achieved with mesotrione and acetochlor in combination with atrazine applied preemergence. All three hybrids recorded the highest grain yields (4,370 to 5,870 kg ha−1) with atrazine and mesotrione applied separately, and when they were combined. These results suggested that atrazine, mesotrione, or a mixture of atrazine + mesotrione applied preemergence may be safely used for Palmer amaranth and green foxtail control with newly developed pearl millet hybrids.